Feasibility of Individual Carotenoid Quantification in Mixtures Using UV-Vis Spectrophotometry with Multivariate Curve Resolution Alternating Least Squares (MCR-ALS) - Achir, Nawel; Servent, Adrien; Soto, Marvin; Dhuique-Mayer, Claudie (Journal of Spectroscopy, 2022)
A fast and low-cost analytical method to determine the concentrations of carotenoids (β-carotene, lutein, and lycopene) from mixed standard solutions or from fruit extracts (kiwi fruits, tomato paste, pink grapefruit juice, kiwi-pineapple smoothie, and apricot nectar) was tested. The methodology was based on UV-Vis spectrophotometry and Multivariate Curve Resolution-Alternating Least Squares (MCR-ALS). Results showed that relative concentrations of β-carotene, lutein, and lycopene in solvent were successfully determined by this technique with an error inferior to 6%. In real extracts, the procedure succeeded well in identifying the major carotenoid type of the fruit samples but also a more complex profile of a fruit mixture. The results also showed that accuracy of carotenoids determination by UV-Vis spectrophotometry-MCR-ALS in fruit extracts was conditioned by their spectral characteristics (III/II ratios and λmax), their relative proportion, and the extract purity.